Pengaruh Kedalaman Lubang Tetas terhadap Daya Tetas dan Waktu Inkubasi Telur Maleo - Rimu, La Emi; Mallombasang, Sri Ningsih; Tanari, Mobius (Universitas Tadulako, 2022)
This research aims to determine the appropriate depth of the hatching hole in order to increase hatchability and shorten the incubation time for Maleo eggs. The research design used a Completely Randomized Design (CRD) with 4 hatching tests with depths: K1 (40 cm), 50 cm, 60 and 70 cm with 5 repetitions. The variables observed consisted of hatching hole temperature, hatching humidity, incubation time and hatchability. Data were analyzed using SPSS Version 2.1. Anova results showed that the treatment had a high significant effect (P<0.01) on hatch hole temperature and hatch hole humidity. The conclusion from the results of this research is that the treatment that provides the shortest hatching time and the highest hatchability is the K3 treatment (60cm depth) with an average hatching temperature of 33.40 0C (range 33-34 0C) and an average hatching humidity of 62.40% (range 60 – 74%), in the Maleo Saluki Population Development Demonstration TNLL because it is capable of hatching up to 100% with an average incubation time of 69 days (range 65 – 74 days).